Green Wasathiyyah Campus as a Space for Transforming Islamic Wasathiyyah Values through Ecotheology - Nugroho, Muhammad Aji; Billah, Arif; Rahmah, Yulinar Aini; Trisnadariawati, Linda Putri (Analisa: Journal of Social Science and Religion, 2025)
This study aims to examine the transformation of students' attitudes towards Islamic wasathiyyah values and ecological awareness from an eco-theological perspective, emphasizing a scientific approach in the Faculty of Tarbiyah and Teacher Training (FTIK) at UIN Salatiga. The background of this study is based on the increasing global challenges such as religious intolerance and environmental degradation, which demand an integrative response from Islamic education. Through a scientific approach, Islamic values are integrated with the principles of social sciences, pedagogy, and environmental sustainability to form moderate, inclusive, critical, participatory, and ecologically responsible attitudes. This study employs a descriptive qualitative method, utilizing triangulation techniques through in-depth interviews, participatory observation, and analysis of curriculum documents and RPS to collect data systematically. The study's results indicate a shift in students' attitudes, from a normative understanding to more environmentally conscious and socially just practices. However, challenges remain, such as weak religious-based ecological literacy, suboptimal integration of cross-curricular values, and minimal responsive faculty policies. These findings indicate great potential in developing a thematic curriculum based on wasathiyyah values and an interdisciplinary approach. The conclusion emphasizes the need for curriculum reform, increasing the capacity of educators and teaching staff, as well as strengthening an academic culture based on research and values, to sustainably and scientifically internalize the values of wasathiyyah and eco-theology.